Living Donor Liver Transplantation as a Backup Procedure: Treatment Strategy for Hepatocellular Adenomas Requiring Complex Resections. (17th February 2022) - Fonseca, Eduardo A.; Feier, Flavia; Vincenzi, Rodrigo; Candido, Helry L. L.; Azambuja, Rodrigo L.; Payao, Fabio; Benavides, Marcel R.; Roda, Karina M. O.; Leite, Katia M. R.; Ribeiro, Cristiane M. F.; Begnami, Maria D.; Zurstrassen, Charles E.; et al.
Abstract : Background & Aims . The most dangerous complications of hepatocellular adenomas are hemorrhage and malignant transformation, both of which require surgical treatment. The surgical treatment strategy for patients with benign large or central tumors is challenging because complex liver resections are required. The strategy of using a live donor as a backup procedure is described in this series. Methods . We present a series of three patients with large hepatocellular adenoma lesions showing a central location, for which the living donor liver transplantation strategy was used as a backup procedure. Results . Hepatocellular adenoma was confirmed by biopsy in all patients. Surgical resection was indicated because of the patients' symptoms and lesion size and growth. All patients had a lesion that was central or in close contact with major vessels. The final decision to proceed with the resection was made intraoperatively. A live donor was prepared for all three patients. Two patients underwent portal vein embolization associated with extended hepatectomy, and a total hepatectomy plus liver transplantation with a living donor was performed in one patient. All patients had good postoperative outcomes. Conclusions . In the treatment of hepatocellular adenomas for which complex resections are necessary and resectability can only be confirmed intraoperatively, surgical safety can be improved through the use of a living donor backup. Center expertise with living donor liver transplantation is paramount for the success of this approach.